Makna Suluk pada Lansia Anggota Jamaah Tarekat Naqsyabandiyah - Misykah N. Birohmatika; R. Rachmy Diana (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
This study aims to know the meaningful of dynamics life through the spiritual process in the eldery of the member of Congregation Jemaah Naqsyabandiyah that has followed suluk. Suluk is ritual series in mysticism to get the next stages or to improve “maqam” for the retire ways from the world and some rituals that are directed by murshid with the sole purpose of approach to Allah SWT. The kind of the research is fenomenologik and the characteristic of the research is Qualitative descriptive. The data are collected using observation and interview. Tematik analysis was used in data analysis. This research took 3 people as informants. The result showed that the semeleh concept emerged from the meaning of mysticism. Semeleh illustrated with submission of life, sobriety, confidence, sincerity to receive God's destiny, readiness to face death and no longer prioritize the worldly affairs. Impacts that arise in the behavior of the discipline, commitment and consistency in worship.Keywords: Meaning, Suluk